Psychological and spiritual wellbeing of family caregivers of children with cancer at a teaching hospital in Ghana - Beatrice A.A. Bekui; Lydia Aziato; Lillian Akorfa Ohene; Magdalena S. Richter (Elsevier, 2020)
Background: The World Health Organization (WHO) recognizes the significance of families' caregiving roles for sick children, especially in the case of cancer and other chronic diseases. Objectives: This study aimed to explore the psychological and spiritual wellbeing of family caregivers of children with cancer at a teaching hospital in Ghana. Methods: A qualitative exploratory descriptive design was employed. Purposive sampling technique was used to recruit participants who met the inclusion criteria. A total of thirteen (13) participants were interviewed one-on-one, using a semi-structured interview guide. All interviews were audio taped and transcribed verbatim. Data were analyzed using thematic content analysis. Findings: It was identified that caregiving affected the psychological and spiritual wellbeing of family caregivers. Four subthemes emerged as psychological experiences and these include; fear and anxiety, distress and sadness, blame, confusion and helplessness. Spiritual wellbeing focused on inner strength and exercise of faith. Three subthemes emerged as spiritual wellbeing: hope, meaning to life, and religious rituals. Conclusions: Several challenges mark the care trajectory of child cancer patients which impinge on the psychological wellbeing of family caregivers. In the light of limited psychological care for family caregivers of child cancer patients, caregivers (mostly mothers) rely on their religious faith and rituals to invoke deeper spiritual understanding and purpose to life.